The Advantages of Levodopa-Carbidopa Intestinal Gel for Patients with Advanced Parkinson’s Disease: A Systematic Review - Zhang XR; Jiang ZY; Zhang ZR; Chen HJ; Wu K; He JC; Xie CL (Dove Medical Press, 2020)
Xing-Ru Zhang, 1,* Zhi-Yu Jiang, 2,* Zeng-Rui Zhang, 3 Hui-Jun Chen, 1 Ke Wu, 4 Jin-Cai He, 1 Cheng-Long Xie 1 1The Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, People’s Republic of China; 2The Department of General Surgery, The Sir Run Run Shaw Hospital, Medical College of Zhejiang University, Hangzhou 310000, People’s Republic of China; 3Department of Neurology, Huzhou Central Hospital, Huzhou 313000, People’s Republic of China; 4Zhejiang Provincial Key Laboratory of Aging and Neurological Disorder Research, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cheng-Long Xie; Jin-Cai He Tel/Fax +86 577 88 83 2693Email cl_xie1987@sohu.com; hjc@wmu.edu.cnBackground: Levodopa-carbidopa intestinal gel (LCIG) is a new type of administration that results in steadier levodopa plasma concentrations in advanced Parkinson’s disease (PD) patients and effectively reduces poor mobility and dyskinesia.Methods: Electronic databases were searched up to January 1, 2018. The inclusion criteria for this review were as follows: LCIG vs oral medication in advanced PD patients.Results: Five trials, with a total of 198 patients, met all the inclusion criteria. The quality score of these studies ranged from 3 to 5. Two clinical trials showed that compared with oral medication, LCIG had a better treatment effect on on-time with troublesome dyskinesia (TSD) (p = 0.02) and on-time without TSD (p < 0.00001) in advanced PD patients. In addition, four of the 5 studies showed that the LCIG may have better efficacy than oral medication for improving the scores of the UPDRS, and two studies found that LCIG demonstrated better efficacy for improving the PDQ-39 scores. The video recording results indicated a potential decline in both dyskinesia and the “off” state in LCIG-treated patients. The incidence of adverse events was not significantly different between the LCIG and oral medication groups.Conclusion: Compared with oral treatment, LCIG exerts its effectiveness, mostly by reducing the time of on-time with TSD, increasing the time of on-time without TSD and scores of UPDRS and PDQ-39. It is suggesting that LCIG was likely to be a new type of administration used in clinical applications. However, due to methodological flaws, these findings should be viewed with caution, and more RCTs are needed in the field to complement our findings.Keywords: Levodopa-carbidopa intestinal gel, Parkinson’s disease, oral medication, clinical trials, systematic review